Presentation is loading. Please wait.

Presentation is loading. Please wait.

y x y = x + 2 y = x + 4 y = x – 1 y = 6x – 3 y = 2x y = ½x y = 3x + 1

Similar presentations


Presentation on theme: "y x y = x + 2 y = x + 4 y = x – 1 y = 6x – 3 y = 2x y = ½x y = 3x + 1"— Presentation transcript:

1 y x y = x + 2 y = x + 4 y = x – 1 y = 6x – 3 y = 2x y = ½x y = 3x + 1
Graphs of Algebraic Equations 2 Complete each table, then plot the points on the graph, complete the line and label it y x 1 2 3 4 5 Y y = x + 2 9 8 x 1 2 3 4 5 Y y = x + 4 7 6 x 1 2 3 4 5 Y y = x – 1 5 4 x 1 2 3 4 5 Y 3 y = 6x – 3 2 1 y = 2x x 1 2 3 4 5 Y -8 -7 -6 -5 -4 -3 -2 -1 1 2 3 4 5 6 7 8 x -1 y = ½x x 1 2 3 4 5 Y -2 -3 -4 y = 3x + 1 x 1 2 3 4 5 Y -5 -6 Y=x² x 1 2 3 4 5 Y -7 -8 y = x³ x 1 2 3 4 5 Y -9 x 1 2 3 4 5 Y y = -x – 2


Download ppt "y x y = x + 2 y = x + 4 y = x – 1 y = 6x – 3 y = 2x y = ½x y = 3x + 1"

Similar presentations


Ads by Google